The Effectiveness of the Direct Instruction Learning Model on the Ability of Badminton Basic Techniques at SMA - Abd. Halim; Apriyanto; Sayida Khoiratun Nisak; Titik Haryanti; Muhammad Rifai (PT Inovasi Pratama Internasional, 2024)
This study aims to investigate the impact of the direct instruction learning (DI) model on the acquisition of fundamental badminton skills in a secondary education context. Specifically, it seeks to determine whether DI enhances students' understanding and proficiency in badminton techniques at the secondary education level. This study aimed to ascertain the impact of the direct instruction (DI) learning model on the acquisition of basic badminton skills among students in class XI IPA 3 at SMAN 6 Jakarta. The research method employed was that of an experiment with a pretest-posttest design. The sample was selected using purposive sampling, with a total of 33 individuals included. Data collection techniques employed observation of non-badminton basic skills, with an increase based on pretest and posttest data of 46.24%. Parametric analysis was conducted, which demonstrated a significant value of 0.000 in the sign test for the research instrument's basic skills test grids. The data analysis utilized an alpha level of 0.05, indicating that the DI learning model affects learning outcomes.